Clima organizacional y satisfacción laboral de los trabajadores en corporación hotelera y turística del amazonas de Iquitos 2022 - Guzman Paliza, Myriam Alejandra (2023)
The general objective of the research was to determine the relationship between the organizational climate and the job satisfaction of the workers in the Hotel and Tourism Corporation of the Amazonas of Iquitos, 2022, in which a study of applied type, correlational level and design was chosen. experimental, which was made up of 46 workers. For data collection, a questionnaire of questions was used. Therefore, the work concluded that the organizational climate is qualified as regular by 28%, since sometimes an adequate interpersonal and work relationship is managed, and sometimes a stimulus is given to organizational development, adequate leadership is managed. . For its part, job satisfaction is rated as regular by 30%, since the respondents are neutral with the indicator of their own work methods, and dissatisfied with the recognition for doing a good job. Likewise, it was determined that the organizational climate is related to job satisfaction contrasted by a coefficient of 0.864 Spearman's Rho, a coefficient of 0.853 was also determined for organizational behavior; for organizational structure a coefficient of 0.882; and for management style a coefficient of 0.884, each of them is significantly related to job satisfaction.